2017
DOI: 10.1111/codi.13555
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for treatment of chronic anal fissure: adipose‐derived regenerative cells – a pilot study

Abstract: The application of ADRC may be an alternative to lateral sphincterotomy and a reliable procedure which avoids faecal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 38 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…To date, there are 11 active or recruiting registered studies involving ADSCs as an intervention in conditions such as knee OA and chronic kidney disease ( 256 ). Data disclosed hitherto, mostly by pilot studies, show that—despite not living up fully to their regenerative rationale—ADSCs have shown a promising potential in multiple settings, including ischemic heart disease ( 73 , 74 ), acute myocardial infarction ( 257 ), knee OA ( 258 , 259 ), peripheral vascular disease ( 260 ), SS-associated ulcers ( 261 , 262 ), ischemic diabetic feet ( 252 ), urogenital conditions ( 263 , 264 ), and breast cancer-associated lymphedema ( 265 ). For example, an early-phase placebo-controlled trial has shown that the intracoronary infusion of ADSCs is well tolerated, improves left ventricular ejection fraction (LVEF), and reduces infarct size after 6 months of follow-up in patients with acute myocardial infarction ( 257 ).…”
Section: Clinical Benefits Of Cell Therapy By Select Fieldsmentioning
confidence: 99%
“…To date, there are 11 active or recruiting registered studies involving ADSCs as an intervention in conditions such as knee OA and chronic kidney disease ( 256 ). Data disclosed hitherto, mostly by pilot studies, show that—despite not living up fully to their regenerative rationale—ADSCs have shown a promising potential in multiple settings, including ischemic heart disease ( 73 , 74 ), acute myocardial infarction ( 257 ), knee OA ( 258 , 259 ), peripheral vascular disease ( 260 ), SS-associated ulcers ( 261 , 262 ), ischemic diabetic feet ( 252 ), urogenital conditions ( 263 , 264 ), and breast cancer-associated lymphedema ( 265 ). For example, an early-phase placebo-controlled trial has shown that the intracoronary infusion of ADSCs is well tolerated, improves left ventricular ejection fraction (LVEF), and reduces infarct size after 6 months of follow-up in patients with acute myocardial infarction ( 257 ).…”
Section: Clinical Benefits Of Cell Therapy By Select Fieldsmentioning
confidence: 99%
“…Clinically, autologous cSVF has been used for many different clinical indications such as to regenerate and repair bone and cartilage in concert with bone grafting , in the treatment of osteoarthritis , and in the management of peripheral vascular disease sequela such as chronic wounds . Cellular SVF has been very effective in the treatment of perianal and recto vaginal fistulas as well as for Crohn's disease , in the treatment for the sequela of radiation injury such as fibrosis, atrophy, retraction, and soft tissue ulceration and to reduce aberrant scar formation . The homing mechanism of cSVF to tumor sites makes them a promising vector for therapeutic delivery to tumors and metastatic niches .…”
Section: Liposuction Aspirate Fluid (Infranatant) Processingmentioning
confidence: 99%
“…Pain particularly may reduce the quality of life of patients ( 7 , 8 ). Chronic anal fissure is accompanied by hypertrophic papilla along whose edge internal sphincter muscle fibres become visible ( 9 ). Physical and chemical agents are used basically to reduce sphincter pressure for treating acute anal fissure.…”
Section: Introductionmentioning
confidence: 99%